The Role of Internal Financing in Mediating the Influence of Managerial Overconfidence on Investment Decisions; Evidence from Manufacturing of Indonesia - Zaludin; Sarita, Buyung; Takdir S, Dedy; Sujono, Sujono (International Journal of Management and Education in Human Development, 2021)
This study aims to examine the influence of managerial overconfidence and internal financing on investment decisions, the effect of managerial overconfidence on internal financing, and the role of internal financing mediating the influence of managerial overconfidence on investment decisions. The research population is manufacturing companies listed on the Indonesia Stock Exchange. The research sample is 44 companies with 264 observable data. The result of this research is that managerial overconfidence and internal financing will increase firm investment, managerial overconfidence prefers to retain earnings as retained earnings rather than distribute to shareholders as dividends, and the high availability of internal funds causes managerial overconfidence to increase firms’ investment. The results show that internal financing can fund business opportunities and reduce capital shortages, especially in firms with excessive managerial overconfidence.